Utilization of Palm Oil Clinker as Cement Replacement Material - Kanadasan, J.; Razak, H.A. (MDPI, 2015)
The utilization of waste materials from the palm oil industry provides immense benefit to various sectors of the construction industry. Palm oil clinker is a by-product from the processing stages of palm oil goods. Channelling this waste material into the building industry helps to promote sustainability besides overcoming waste disposal problems. Environmental pollution due to inappropriate waste management system can also be drastically reduced. In this study, cement was substituted with palm oil clinker powder as a binder material in self-compacting mortar. The fresh, hardened and microstructure properties were evaluated throughout this study. In addition, sustainability component analysis was also carried out to assess the environmental impact of introducing palm oil clinker powder as a replacement material for cement. It can be inferred that approximately 3.3% of cement production can be saved by substituting palm oil clinker powder with cement. Reducing the utilization of cement through a high substitution level of this waste material will also help to reduce carbon emissions by 52%. A cleaner environment free from pollutants can be created to ensure healthier living. Certain industries may benefit through the inclusion of this waste material as the cost and energy consumption of the product can be minimized.